Insulated monopole sensor for determination of moisture content in hevea rubber latex - Ansarudin, Farizah (2012)
The thesis describes an investigation of the use of insulated monopole sensor as a new technique for the determination of moisture content in hevea rubber latex at microwave frequencies from 100 MHz to 5 GHz. The technique is investigated from the viewpoint of assessing its suitability as a simple, quick, non-destructive and flexible approach to determination of moisture content with comparable accuracy to the standard oven drying method. The analytical King’s model was used to calculate approximately the variation in the reflection coefficients of the monopole sensor with frequency for various lengths of antenna, aspect ratios and type of insulated material. Extensive measurement results are provided in the thesis. The measured and calculated magnitude of the reflection coefficient using King’s model were found to be in good agreement at 1 GHz for all samples of various percentages of moisture content but extendable to 3 GHz for moisture content less than 54.15%. However,lowest error between measured and calculated phase was found in the frequency range from 2 GHz to 3 GHz coinciding with the profile of the variation in loss factor with frequency. Regression analyses were carried out to relate moisture content to magnitude, phase shift, conductance, susceptance, frequency shift of G-B peaks at different frequencies. These empirical equations were tested on 37 new samples by comparing the predicted moisture content with the actual moisture content obtained from oven drying method. It has been found that all the three empirical equations with good accuracy based on magnitude, phase shift and conductance shared similar operating frequency 0.52 GHz. The phase shift technique was found be to be most accurate in the determination of moisture content within 1.37% when compared to actual moisture content obtained using standard oven drying method.